Comparison of immunogenicity and clinical effectiveness between BNT162b2 and ChAdOx1 SARS-CoV-2 vaccines in people with end-stage kidney disease receiving haemodialysis: A prospective, observational cohort study - Paul Martin; Sarah Gleeson; Candice L. Clarke; Tina Thomson; Helena Edwards; Katrina Spensley; Paige Mortimer; Stacey McIntyre; Alison Cox; Graham Pickard; Liz Lightstone; David Thomas; et al. (Elsevier, 2022)
Summary: Background: People with end-stage kidney disease, including people on haemodialysis, are susceptible to greater COVID-19 related morbidity and mortality. This study compares the immunogenicity and clinical effectiveness of BNT162B2 versus ChAdOx1 in haemodialysis patients. Methods: In this observational cohort study, 1021 patients were followed-up from time of vaccination until December 2021. All patients underwent weekly RT-PCR screening. Patients were assessed for nucleocapsid(anti-NP) and spike(anti-S) antibodies at timepoints after second(V2) and third(V3) vaccinations. 191 patients were investigated for T-cell responses. Vaccine effectiveness (VE) for prevention of infection, hospitalisation and mortality was evaluated using the formula VE=(1-adjustedHR)x100. Findings: 45.7% (467/1021) had evidence of prior infection. There was no difference in the proportion of infection-naïve patients who seroconverted by vaccine type, but median anti-S antibody titres were higher post-BNT162b2 compared with ChAdOx1; 462(152-1171) and 78(20-213) BAU/ml respectively, p<0.001.  Concomitant immunosuppressant use was a risk factor for non-response, OR 0.12[95% CI 0.05-0.25] p<0.001.  Post-V3 (all BNT162b2), median anti-S antibody titres remained higher in those receiving BNT162b2 versus ChAdOx1 as primary doses; 2756(187-1246) and 1250(439-2635) BAU/ml respectively, p=0.003.Anti-S antibodies waned over time. Hierarchical levels of anti-S post-V2 predicted risk of infection; patients with no/low anti-S being at highest risk. VE for preventing infection, hospitalisation and death was 53% (95% CI 6-75), 77% (95% CI 30-92) and 93% (95% CI 59-99) respectively, with no difference seen by vaccine type. Interpretation: Serum anti-S concentrations predict risk of breakthrough infection. Anti-S responses vary dependent upon clinical features, infection history and vaccine type. Monitoring of serological responses may enable individualised approaches to vaccine boosters in at risk populations. Funding: National Institute for Health Research (NIHR) Biomedical Research Centre based at Imperial College Healthcare NHS Trust and Imperial College London.